Effects of Vitamin E-Stabilized Ultra High Molecular Weight Polyethylene on Oxidative Stress Response and Osteoimmunological Response in Human Osteoblast - Massaccesi, Luca; Ragone, Vincenza; Papini, Nadia; Goi, Giancarlo; Corsi Romanelli, Massimiliano Marco; Galliera, Emanuela (Frontiers in Endocrinology, 2019)
High Crosslink process was introduced in the development of joint prosthetic devices, in order to decrease the wear rate of ultrahigh molecular weight polyethylene (UHMWPE) but it also triggers the formation of free radicals and oxidative stress, which affects the physiological bone remodelling, leading to osteolysis. Vitamin E stabilization of UHMWPE was proposed to provide oxidation resistance without affecting mechanical properties and fatigue strength. The aim of this study is to evaluate the antioxidant effect of vitamin E added to UHMWPE on oxidative stress induced osteolysis, focusing in particular on the oxidative stress response in correlation with the production of osteoimmunological markers, Sclerostin and DKK-1 and the RANKL/OPG ratio compared to conventional UHMWPE wear debris. Human osteoblastic cell line SaOS2 were incubated for 96 hours with wear particles derived from crosslinked and not crosslinked Vitamin E-stabilized, UHMWPE without Vitamin E and growth medium as control. Cellular response to oxidative stress, compared to not treat cells, was evaluated in terms of proteins O-GlcNAcylation, cellular levels of OGA and OGT proteins by immunoblotting . O-GlcNAcylation and its positive regulator OGT levels are increased in presence of Vitamin E blended UHMWPE, in particular with not crosslinked Vit E stabilized UHMWPE. Conversely , the negative regulator OGA increase in the presence of UHMWPE not blended with Vitamin E.. Vitamin E-stabilized UHMWPE induced a decrease of RANKL/OPG ratio compared to UHMWPE without Vitamin E, and the same effect was observed for Sclerostin, while DKK-1 was not significantly affected. In conclusion, Vitamin E stabilization of UHMWPE increased osteoblast response to oxidative stress, inducing cellular mechanism aimed to cell survival. Vitamin E antioxidant effect influences the secretion of osteoimmunological factors, shifting the bone turnover balance toward bone protection’s stimuli. This suggests that Vitamin E-Stabilization of UHMWPE could contribute to reduce oxidation-induced osteolysis and the consequent loosening of the prosthetic devices, therefore improving the longevity of total joint replacements.